Assessment of Potential Clinical Role for Exome Sequencing in Schizophrenia. (21st May 2019) - Balakrishna, Thivia; Curtis, David
Abstract: Background: There is increasing evidence that certain genetic variants increase the risk of schizophrenia and other neurodevelopmental disorders. Exome sequencing has been shown to have a high diagnostic yield for developmental disability and testing for copy number variants has been advocated for schizophrenia. The diagnostic yield for exome sequencing in schizophrenia is unknown. Method: A sample of 591 exome-sequenced schizophrenia cases and their parents were screened for disruptive and damaging variants in autosomal genes listed in the Genomics England panels for intellectual disability and other neurological disorders. Results: Previously reported disruptive de novo variants were noted in SETD1A, POGZ, SCN2A, and ZMYND11 . Although the loss of function of ZMYND11 is a recognized cause of intellectual disability, it has not previously been noted as a risk factor for schizophrenia. A damaging de novo variant of uncertain significance was noted in NRXN1 . A previously reported homozygous damaging variant in BLM is predicted to cause Bloom syndrome in 1 case and 1 case was homozygous for a damaging variant in MCPH1, a result of uncertain significance. There were more than 400 disruptive and damaging variants in the target genes in cases but similar numbers were seen among untransmitted parental alleles and none appeared to be clinically significant. Conclusions: The diagnostic yield from exome sequencing in schizophrenia is low. Disruptive and damaging variants seen in known neuropsychiatric genes should not be automatically assumed to have an etiological role if observed in a patient with schizophrenia.